A c. 1710 Ma mafic sill emplaced into a quartzite and calcareous series from Ighrem, Anti-Atlas – Morocco: Evidence that the Taghdout passive margin sedimentary group is nearly 1 Ga older than previously thought. (March 2017) - Ikenne, Moha; Söderlund, Ulf; Ernst, Richard E.; Pin, Christian; Youbi, Nasrrddine; El Aouli, El Hassan; Hafid, Ahmid
Abstract: The Taghdout Group is a passive margin sequence deposited during rifting and break-up of the northern margin of the West African craton (WAC), culminating with the creation of an oceanic basin between the northern edge of the WAC and an unknown terrane. However, the age of this passive margin has been poorly constrained. It was previously thought to be c. 800–1000 Ma on the basis of age of the contact metamorphosed host rocks of the associated mafic dykes (Rb/Sr, 789 ± 10 Ma). However, with the U-Pb dating of numerous dyke swarms in the Anti-Atlas Inliers, at c. 870, 1416-1380, 1650, 1750, and 2040 Ma, it was suggested by Youbi et al. (2013) that the Taghdout Group could be Mesoproterozoic in age, with a preference for an age of 1750 Ma. In order to test this idea, a mafic sill within the Taghdout Group has been dated by the ID-TIMS U-Pb method on baddeleyite, yielding an approximate age of c. 1710 Ma. This preliminary age confirms that the Taghdout Group is much older than previously thought. Further geochronology work is required to determine whether this c. 1710 Ma age represents a new intraplate event in the WAC or whether more concordant data could yield an age closer to the known WAC LIP event of c. 1750 Ma. With this result we propose a new lithostratigraphic framework for the Proterorozoic in the Anti-Atlas. Highlights: A mafic sill emplaced into a quartzite and calcareous series from Ighrem in the Anti-Atlas is dated at c 1710 Ma. The Taghdout passive margin sedimentary group is nearly 1 Ga older than previously thought. A new lithostratigraphic framework is proposed for Proterozoic in the Anti-Atlas. Three domains of different ages have been recognized, their common history started from the Ediacaran, as attested by the Supergroup Ouarzazate that extend across the Anti-Atlas.